Egg consumption and risk of coronary heart disease and stroke: dose-response meta-analysis of prospective cohort studies - Rong, Ying (BMJ Publishing Group Ltd., 2013)
Objective To investigate and quantify the potential dose-response association between egg consumption and risk of coronary heart disease and stroke. Design Dose-response meta-analysis of prospective cohort studies. Data sources PubMed and Embase prior to June 2012 and references of relevant original papers and review articles. Eligibility criteria for selecting studies Prospective cohort studies with relative risks and 95% confidence intervals of coronary heart disease or stroke for three or more categories of egg consumption. Results Eight articles with 17 reports (nine for coronary heart disease, eight for stroke) were eligible for inclusion in the meta-analysis (3 081 269 person years and 5847 incident cases for coronary heart disease, and 4 148 095 person years and 7579 incident cases for stroke). No evidence of a curve linear association was seen between egg consumption and risk of coronary heart disease or stroke (P=0.67 and P=0.27 for non-linearity, respectively). The summary relative risk of coronary heart disease for an increase of one egg consumed per day was 0.99 (95% confidence interval 0.85 to 1.15; P=0.88 for linear trend) without heterogeneity among studies (P=0.97, I(2)=0%). For stroke, the combined relative risk for an increase of one egg consumed per day was 0.91 (0.81 to 1.02; P=0.10 for linear trend) without heterogeneity among studies (P=0.46, I(2)=0%). In a subgroup analysis of diabetic populations, the relative risk of coronary heart disease comparing the highest with the lowest egg consumption was 1.54 (1.14 to 2.09; P=0.01). In addition, people with higher egg consumption had a 25% (0.57 to 0.99; P=0.04) lower risk of developing hemorrhagic stroke. Conclusions Higher consumption of eggs (up to one egg per day) is not associated with increased risk of coronary heart disease or stroke. The increased risk of coronary heart disease among diabetic patients and reduced risk of hemorrhagic stroke associated with higher egg consumption in subgroup analyses warrant further studies.